Women’s Empowerment Through Small Farmers’ Cooperatives: A Case Study from Eastern Nepal - Poudel, Gehanath; Pokharel, Binod (Journal of Advanced Academic Research, 2018)
Small farmers cooperative limited (SFCL) is one of the very effective microcredit programs. It supports the rural farmer especially poor, marginalized, disadvantage and women of society by providing the saving and credit facilities. It has aimed to improve the socio-economic status of people and reduce the poverty level. The study aims to identify the contribution of SFCL on socio-cultural and political empowerment of Nepalese women. The study was conducted in Ilam district among the 522 women beneficiaries of SFCL. The data were collected by applying the mixed method. Census method was used for this study. The analysis of data found that there was significant difference in socio-cultural and political empowerment of women after involving in SFCL program. Women have been empowered to maintain the social relationship, reduce the gender disparity, involve in social program, and participate in political program through SFCL activities. Women have expanded their network of relationship through saving and credit program. This study argues that women’s access to economic resources changes their social status at household and community level. The study shows the need of expansion of SFCL program in hard-to-reach areas also to empower the socially disadvantaged groups.